Photo-electrochemical and ozonation process to degrade ciprofloxacin in synthetic municipal wastewater, using C, N-codoped TiO2 with high visible-light absorption. Issue 3 (June 2022) - Palomares-Reyna, Daniela; Carrera-Crespo, Juan E.; Sosa-Rodríguez, Fabiola S.; García-Pérez, Ulises M.; Fuentes-Camargo, Iliana; Lartundo-Rojas, Luis; Vazquez-Arenas, Jorge
Abstract: Carbon, nitrogen-codoped TiO2 nanoroughness surfaces (CN-TiNRS) are successfully synthesized through electrochemical anodization at 50, 70 and 90 V (50 V-CN-TiNRS, 70 V-CN-TiNRS, and 90 V-CN-TiNRS, respectively), with the aim of shifting their absorption capacities to the visible-light region. The analysis by X-ray diffraction (XRD) and scanning electron microscopy (SEM) indicate that a TiO2 film with a major proportion of crystalline anatase and nanoroughness morphology is formed on the entire surface of all photoelectrodes. Carbon and nitrogen elements are detected by X-ray photoelectron spectroscopy (XPS) analysis for all samples, obtaining similar weight percentages. The best photoelectrochemical performance is reached for the 70 V-CN-TiNRS electrode subjected to Xe lamp radiation. Accordingly, this photocatalyst is chosen to perform all the ciprofloxacin (CIP) degradation tests in distilled water, involving the following methods: photocatalysis (PC), photoelectrocatalysis (PEC), Ozone (O3 ), photocatalytic ozonation (PCO) and photoelectrocatalytic ozonation (PECO). Degradation tests are additionally conducted in synthetic municipal wastewater (SWW) using PECO, to analyze its oxidation capacity in a real scenario (i.e. organic composition matrix). All techniques revealed that the highest CIP removal occurs with PECO, decreasing TOC by almost 86.79% (95% degradation by HPLC) after 90 min of treatment, thus, exploiting the intrinsic advantages of single PEC and O3 . The radical trapping technique reveals that superoxide radicals (O2 - ), holes (h + ) and hydroxyl radicals (OH ) are responsible of the CIP abatement in the PECO. Reaction mechanisms are proposed for the production of these oxidants, while the CIP degradation pathway is rationalized using HPLC experiments. A toxicity test of the treated water is carried out after the process with PECO by means of germination with sativa lettuce seeds. Graphical Abstract: ga1 Highlights: C and N codoping in TiO2 surfaces shift its absorption to visible-light region. Electrode photocurrent depends on C and N contents, and nanoroughness surface. Photoelectrocatalytic ozonation degrades CIP faster compared to single methods. Photoelectrocatalytic ozonation displays the highest CIP mineralization. Turbidity in synthetic municipal wastewater hampers the CIP elimination.